VeloxChem: A Python‐driven density‐functional theory program for spectroscopy simulations in high‐performance computing environments. (11th December 2019) - Rinkevicius, Zilvinas; Li, Xin; Vahtras, Olav; Ahmadzadeh, Karan; Brand, Manuel; Ringholm, Magnus; List, Nanna Holmgaard; Scheurer, Maximilian; Scott, Mikael; Dreuw, Andreas; Norman, Patrick
Abstract: An open‐source program named VeloxChem has been developed for the calculation of electronic real and complex linear response functions at the levels of Hartree–Fock and Kohn–Sham density functional theories. With an object‐oriented program structure written in a Python/C++ layered fashion, VeloxChem enables time‐efficient prototyping of novel scientific approaches without sacrificing computational efficiency, so that molecular systems involving up to and beyond 500 second‐row atoms (or some 10, 000 contracted and in part diffuse Gaussian basis functions) can be routinely addressed. In addition, VeloxChem is equipped with a polarizable embedding scheme for the treatment of the classical electrostatic interactions with an environment that in turn is modeled by atomic site charges and polarizabilities. The underlying hybrid message passing interface (MPI)/open multiprocessing (OpenMP) parallelization scheme makes VeloxChem suitable for execution in high‐performance computing cluster environments, showing even slightly beyond linear scaling for the Fock matrix construction with use of up to 16, 384 central processing unit (CPU) cores. An efficient—with respect to convergence rate and overall computational cost—multifrequency/gradient complex linear response equation solver enables calculations not only of conventional spectra, such as visible/ultraviolet/X‐ray electronic absorption and circular dichroism spectra, but also time‐resolved linear response signals as due to ultra‐short weak laser pulses. VeloxChem distributed under the GNU Lesser General Public License version 2.1 (LGPLv2.1) license and made available for download from the homepage https://veloxchem.org . This article is categorized under: Software > Quantum Chemistry Electronic Structure Theory > Density Functional Theory Theoretical and Physical Chemistry > Spectroscopy Abstract : With a high degree of code vectorization and parallelization, the VeloxChem program provides a powerful tool to calculate absorptive and dispersive parts of real and complex linear response functions at the level of Kohn–Sham density functional theory, also allowing for a treatment of ultra‐short light pulses.